Insights Into Magma Chamber Processes From the Relationship Between Fabric and Grain Shape in Troctolitic Cumulates - Holness, Marian B.; Morris, Charlotte; Vukmanovic, Zoja; Morgan, Dan J. (Frontiers in Earth Science, 2020)
The strength of foliations defined by shape preferred orientation of plagioclase in troctolitic cumulates from the Skaergaard and Rum intrusions increases as the grains become more tabular, due either to the greater propensity of highly non-equant grains to be re-arranged by magmatic currents or tectonic disruption of poorly consolidated mush, or by the effects of a pre-existing fabric on final grain shape in fully solidified rocks. The stratigraphic evolution of grain shape, microstructures and fabrics in the lower part of the Skaergaard Layered Series records the progressive inflation of the chamber to its final size. The extent of in situ nucleation and growth on the chamber floor decreased upwards through the stratigraphy, due to the development of an insulating blanket of mush on the floor. An upwards increase in fabric strength was a result of the increasing strength of convection of the bulk magma and an increasing contribution to the floor mush of crystals derived from the walls of the magma chamber as the chamber inflated to its final size.